Effect of basal luteinizing hormone (bLH) level on in vitro fertilization/intra-cytoplasmic injections (IVF/ICSI) outcomes in polycystic ovarian syndrome (PCOS) patients - Zhuo Liu; Ke-Hua Wang (BMC, 2023)
Abstract Objective To evaluate the effect of basal luteinizing hormone (bLH) levels on In Vitro Fertilization/Intra-Cytoplasmic Injections (IVF/ICSI) outcomes in polycystic ovary syndrome (PCOS). Methods A total of 256 PCOS patients who underwent IVF/ICSI treatment in our center from January 2018 to January 2022 were analyzed retrospectively. The patients were based on the third quartile (12.455) of the basal LH value was taken as the cut-off value and was divided into high and low LH group: high LH group (LH ≥ 12.455 IU / L) and low LH group (LH < 12.455 IU / L) and the OC group was pretreated with oral contraceptives. The outcomes in ovulation induction and embryo transfer cycles of the three groups were then compared. In addition, factors influencing the number of good quality embryos and the early onset LH peak were analyzed. Results Ages, infertility duration, body mass index (BMI), and basal follicle-stimulating hormone (FSH), and progesterone (P), testosterone (T) levels were not significantly different among the three groups (p > 0.05). However,there were significant differences in basal LH and basal E2 between low LH group and high LH group, and there were significant differences in basal LH between high LH group and OC group (p < 0.05). LH on the antagonist day was significantly different between low LH group and high LH group and between high LH group and OC group (p < 0.05). LH on the hCG (human Chorionic Gonadotropin) day there were significant differences between low LH group and OC group, high LH group and OC group (p < 0.05). The Mode of triggering between the three groups had significant differences between the two groups (p < 0.05). In addition, the number of days from gonadotropin (Gn) initiation to antagonist addition were significantly different among the three groups (p < 0.05). In addition, total Gn doses,the number of oocytes retrieved, the number of Gn days, 2pronucleus (2PN) numbers, number of good quality embryos, and number of high risk OHSS (Ovarian Hyper-stimulation Syndrome), cases with OHSS occurrences were not significantly different among the three groups (p > 0.05). Moreover, the cycle and clinical pregnancy outcomes and the cumulative clinical pregnancy rate and the cumulative live birth rate were not significantly different among the three groups (p > 0.05). LH levels on the day of antagonist addition affected the number of good-quality embryos (B < 0, p < 0.05). However, LH levels on the day antagonist was added were not significantly correlated with basal LH levels (Pearson correlation coefficient = 0.259), the ROC curve was constructed for the logistic prediction model of the early onset LH peak, and the AUC value was 0.747, indicating that the logistic combined model we constructed had a good ability to predict the early onset LH peak. Conclusion Basal LH levels do not affect the pregnancy outcomes in PCOS patients after antagonist protocols. Besides, LH levels on the day of antagonist addition affect the number of good quality embryos for PCOS patients undergoing IVF /ICSI.